2010
DOI: 10.1212/wnl.0b013e3181f73673
|View full text |Cite
|
Sign up to set email alerts
|

Polytherapy increases the risk of infertility in women with epilepsy

Abstract: More than a third (38.4%) of WWE had infertility. The important predictors of infertility were exposure to multiple AEDs, older age, and lower education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 16 publications
1
34
2
2
Order By: Relevance
“…An important contribution to the discussion of fertility in epilepsy thus far is from the Kerala Registry of Epilepsy and Pregnancy. 103 In this registry, young women with epilepsy are followed prospectively and generally try to become pregnant following marriage; a 38% infertility rate was found, and this increased rate of infertility was associated with antiepileptic drug polytherapy versus monotherapy. Several biological reasons could cause decreased fertility in women with epilepsy, including premature ovarian failure, increased rates of anovulatory cycles, and a frequent occurrence of PCOS.…”
Section: Effects Of Antiepileptic Drugs and Seizures On Reproductive mentioning
confidence: 99%
“…An important contribution to the discussion of fertility in epilepsy thus far is from the Kerala Registry of Epilepsy and Pregnancy. 103 In this registry, young women with epilepsy are followed prospectively and generally try to become pregnant following marriage; a 38% infertility rate was found, and this increased rate of infertility was associated with antiepileptic drug polytherapy versus monotherapy. Several biological reasons could cause decreased fertility in women with epilepsy, including premature ovarian failure, increased rates of anovulatory cycles, and a frequent occurrence of PCOS.…”
Section: Effects Of Antiepileptic Drugs and Seizures On Reproductive mentioning
confidence: 99%
“…In this study, WWE exposed to phenobarbital had significant risk of infertility, but no such trend was observed with valproate or other drugs. [4] AEDs can alter the reproductive hormone balance in women by several mechanisms. Valproate is known to alter the sex hormone metabolism and predispose to polycystic ovarian syndrome which in turn could lead to infertility.…”
Section: Infertilitymentioning
confidence: 99%
“…An Indian study that included women with validated epilepsy, reported AED polytherapy as a major risk factor for lack of conception, but this study did not compare birth rates to controls (Sukumaran et al. 2010). However, other studies indicate that controlling for comorbidities may be of greater significance regarding fertility rate than the epilepsy per se (Jalava and Sillanpaa 1997; Olafsson et al.…”
Section: Introductionmentioning
confidence: 99%